REVIEW ON THE GENETIC, BEHAVIORAL AND SOCIAL INCLUSION PARAMETERS OF CHILDREN AND YOUNG PEOPLE WITH AUTISM AND ASD - dos Santos Lins, Mônica; Gomes da Silva Júnior, Evandro; Milleanny Santos Cirilo, Fernanda; dos Santos Araújo, Janderson; Laura da Silva Bila, Ana (Health and Society, 2021)
There are different types of behavioral disorders of a genetic nature that affect human beings, among these we can mention the autism spectrum disorders (ASDs). O ASD is a disorder where its carriers tend to have difficulties in social interaction, repetitive and impulsive behaviors, many times it is violent, also showing many difficulties to develop activities that are constantly practiced easily by other children, VAZ et al (2015). This form several methodologies are being developed for the inclusion of children carrying two disorders in schools of basic education, both as adults in institutions of higher education, since this inclusion will guarantee a better quality of life, as discussed in our work. SILVA (2009). The objective of this work was to carry out a systematic review of items most correlated to behavioral, nutritional and genetic aspects, apart from the conditions of inclusion of two individuals with ASD. In order to obtain the aforementioned objective, we have searched for papers that address these aspects, as well as means of social inclusion of children, young people and adults with Autism Spectrum Disorder (ASD). During the days of searches carried out by the team, and a careful selection by means of reading abstracts and complete reading papers, we had a total of 20 papers, being only selected 6 jobs at the end. The collected results show that ASDs are caused by genetic hazards and that the problems about the behavioral conditions and inclusion had decrease a little by means of the advancement of science and improvement of techniques over a period years.